REPRODUKSI LAGU KR. KEMAYORAN: KONSTRUKSI SUBJEKTIVITAS NYAK INA RASEUKI (UBIET) - Susi Gustina (Institut Seni Indonesia Yogyakarta, 2012)
This article shows the knowledge and cultural perception of an Indonesian woman singer, Nyak Ina Raseuki (Ubiet), that was achieved through her musical experiences in social life and constructed her singing style as her aesthetic mastery (connoisseur). Her singing style is used to reproduce songs from the variety of musical genres so that constructed her subjectivity in Indonesian popular music. One of the songs is analyzed in this article is Kr. Kemayoran, a song in the genre of keroncong. The research questions focus on 1) the construction of knowledge and cultural perception of Ubiet to construct her subjectivity, and 2) Ubiet’s way to explore Kr. Kemayoran so that showed the difference from others. This research used the life history method to understand Ubiet’s knowledge and cultural perception and the critical musicology to analyze the song. The research findings are the connoisseur is not depend only on formal education, but on the variety of musical practices in Ubiet’s life. Besides it, Ubiet’s subjectivity more focused on her musical competencies, i.e. her wide vocal range, the ability to explore many songs with microtones, local ornaments, as well as her ability to follow the development of meter and tonalilty (modulation) that are preceded by the music accompaniment. Keyword: subjectivity, connoisseur, knowledge, cultural perception